Macrophages in Nonalcoholic Fatty Liver Disease: A Role Model of Pathogenic Immunometabolism - Krenkel, Oliver; Tacke, Frank (Seminars in Liver Disease, 2017)
Nonalcoholic fatty liver disease (NAFLD) and its progressive inflammatory form, nonalcoholic steatohepatitis (NASH), are leading causes of liver cirrhosis and hepatocellular carcinoma. Metabolism and inflammation are intimately interrelated in NAFLD/NASH, as expressed by the term immunometabolism. Hepatic macrophages mediate inflammatory responses during metabolic disorders and can stimulate or dismantle liver fibrosis. Their functional diversity is partly explained by heterogeneous macrophage subsets: tissue-resident Kupffer cells and monocyte-derived macrophages. However, macrophages themselves are altered in their functional polarization by dietary composition and metabolic or inflammatory stimuli in NAFLD. The inflammatory polarization of macrophages correlates with changes in core metabolism pathways like oxidative phosphorylation and glycolysis. The availability of nutrients, such as glucose or fatty acids or oxygen also influences macrophage polarization upon danger signal or cytokine reception. Understanding the interplay of metabolism and macrophage function in NASH may open new approaches to therapeutic targeting of these essential modifiers in metabolic liver diseases.
Keywords: metabolism; immunology; chemokine; steatosis; fibrosis